Trade in the WAEMU : Developments and Reform Opportunities - Weisfeld, Hans (IMF Working Papers; Working Paper ;, 2008)
This paper provides an overview of trade reform in the West African Economic and Monetary Union (WAEMU) since 1996 and a quantitative assessment of potential effects on trade patterns and tariff revenue of the current reform agenda. Despite evidence of significant trade complementarities within WAEMU, implementation of the union's current trade regime still suffers from persistent non-tariff barriers and administrative weaknesses. Based on an assessment of prospects for further trade integration, the paper also recommends strengthening the implementation of the present tariff union and supports the plan to extend it to all ECOWAS members. Finally, the paper stresses that an Economic Partnership Agreement with the EU could bring to the region the political momentum needed to address the weaknesses of the current trade regime, while also underlining the corresponding challenges in terms of trade diversion and tariff revenue losses.